MENGHITUNG PERCEPATAN GRAVITASI BANDUL DAN GERAK PARABOLA - Hernelis R (Universitas Riau, 2014)
Experiment to calculate gravitational accceleration has been done using physical pendulum and parabolicmotion principles. One pendulum mass was used namely 0.4 kg .Gravitational acceleration for mass isg =29.295 m/s 2 . These results are close enough to the literature 9.81 m / s . Relative error of this gravitydetermination for each pendulum are 5.3 % .